Thermodynamic mechanism of high energy performance of air source heat pump with coupled liquid-storage to gas-liquid separator. (1st May 2023) - Ma, Longxia; Wang, Fenghao; Wang, Zeyuan; Wang, Zhihua; Zhang, Sheng; Sun, Yongjun
Highlights: Transient loss and defrosting loss of the air source heat pump system coupled with the liquid storage gas–liquid separator were identified. A semi theoretical model based on experimental data for energy efficiency evaluation of air source heat pump system coupled with liquid storage gas–liquid separator was proposed. Evaluated energy efficiency of the air source heat pump coupled with the liquid storage gas–liquid separator was higher than that of the traditional air source heat pump. Path of energy efficiency improvement of air source heat pump system coupled with liquid storage gas–liquid separator was proposed. Abstract: This study proposed a novel air source heat pump system (NASHPs) with coupled liquid-storage and gas-separator to prevent an air source heat pump (ASHP) from frosting. Compared to the original air source heat pump system (OASHPs), the proposed system delayed frost by 30 min and shortened defrosting time by 72 s in a cycle. To further study the mechanism of NASHPs, coefficient of performance (COP), transient losses (heating loss due to frosting and recovery) and defrosting losses (heating loss due to defrosting) of NASHPs and OASHPs were analysed based on experimental data. Furthermore, the thermodynamic perfectibility was introduced to reflect the degree of deviation of the actual operation performance of NASHPs from the theoretical energy efficiency. The maximum reduction of thermodynamic perfectibility in the actual running condition for NASHPs was observed to be approximately 26.5%, which caused the actual continuous energy efficiency of NASHPs to exhibit a certain gap with the energy efficiency of the ideal cycle. The transient loss of NASHPs indicated that the heat loss in the frosting and recovery stages was mainly due to the irreversible loss of the compressor and condenser. Moreover, the defrosting loss of the NASHPs was mainly due to the longer defrosting time and high temperature difference between the supply and return during defrosting. The energy efficiency in the continuous operation of the NASHPs plays a crucial role in the actual operation, and the defrosting loss significantly impacts the actual energy efficiency of the NASHPs compared to transient loss. We believe the results of this study provide a basis for the design and energy efficiency improvement of ASHP systems.